Median Nail Dystrophy due to Habit Tic: A Case Report - Baaniya, Bibisha; Shah, Nidhi (Journal of BP Koirala Institute of Health Sciences, 2021)
Median dystrophy of nails may present with diagnostic difficulty. We present a case of a 30-year old male with multiple serial transverse ridges involving the median part of the bilateral great toe nails and the right thumb nail of approximately 10 years duration. On probing, the patient was found to have the habit of picking over the proximal nail folds. Habit of tic may not be noticed by the patient, however, may be the cause of dystrophy of nails.